ANALISA PARAMETER KEKASARAN PERMUKAAN BAHAN ALUMUNIUM JENIS Al Mg Si 3.6082 DIN 1725 PADA PROSES PEMESINAN CNC MILLING - yunus, moch; Suryana, Didi; Mulyadi, Mulyadi (Politeknik Negeri Sriwijaya, Indonesia, 2012)
Machining process will produce a good product / work in accordance with the instructions specified by the finishing process, while still a lot of operator / mechanic machine tools are still faced with determining machining parameters such as cutting speed, feed rate, and the dept of cut.Melalui results of this study expected to contribute a measure of optimal parameters in CNC operations carried out by means of experiments Milling.Penelitian Al Mg Si material 3.6082 DIN 1725 using a CNC Milling. Any specimen that has been done on a CNC Milling with three variations of cutting speed, feed rate, and the dept of cut measured surface roughness (Ra). From the results of further experimental data are analyzed with regression models to obtain mathematical models. Mathematical models that produced a regression equation Y = 0.880-0.001 n- 0.004 f + 0.316 a 69.8% level of eligibility.